Perbandingan Karakteristik Produk Tahu Berdasarkan Jenis Kedelai pada Produsen Tahu di Sumedang - Saidah, Zumi; Djuwendah, Endah; Yudha, Eka Purna; Fitri, Annisa (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
In general, the characteristics of tofu produced in Sumedang come from two types of soybeans, imported soybeans and local soybeans. This study attempts to examine the characteristics of tofu including texture, color, taste, aroma, water content, and durability. This study is descriptive quantitative, where data collection is carried out through cross-tabulation to see the relationship between soybean types and tofu product characteristics. Through direct observation in the field and conducting interviews with a number of Sumedang tofu producers. The results of the study found that the composition of local soybeans and imported soybeans in producing Sumedang tofu has quite significant differences in forming the characteristics of the tofu produced. Tofu using local soybeans has a soybean flavor and aroma, while tofu processed from imported soybeans has a smoother color and texture. These results can of course provide a real picture for Sumedang tofu producers about choosing the type of soybean according to consumer desires and preferences. Local soybeans can be recommended and educated to tofu producers so that local soybeans are maintained and sustainable.